2020
DOI: 10.21203/rs.3.rs-39988/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characteristics of confirmed cases of COVID-19 admitted at Al-Nahdha hospital, Oman: a cross-sectional descriptive study

Abstract: Abstract Background: With the coronavirus disease 19 (COVID-19) pervading the world, little has been published regarding the hospitalized cases of COVID-19 (confirmed) in the Arabian Gulf countries. This paper describes the socio-demographic, clinical, laboratory, and radiological characteristics, treatment and clinical outcomes of these cases in Al-Nahdha hospital, Oman. Additionally, factors associated with requiring critical care were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Our review now clarifies and confirms some of these effects and, importantly, shows that geography or ethnicity is a major factor. Some researchers had commented on a possible difference in the frequency of chemosensory deficits between East Asians and Caucasians with COVID-19, based on smaller numbers of studies and without considering populations from South Asia. ,,,,,,,, With the much more extensive data sets included in our review (28 878 mostly Caucasians and 9320 Asians), we now show that there indeed is a significant difference in prevalence between Caucasians and Asians: 3-fold higher for smell, taste, and “smell and/or taste” impairment in Caucasians (Figure b).…”
Section: Geography Ethnicity and Geneticsmentioning
confidence: 67%
See 2 more Smart Citations
“…Our review now clarifies and confirms some of these effects and, importantly, shows that geography or ethnicity is a major factor. Some researchers had commented on a possible difference in the frequency of chemosensory deficits between East Asians and Caucasians with COVID-19, based on smaller numbers of studies and without considering populations from South Asia. ,,,,,,,, With the much more extensive data sets included in our review (28 878 mostly Caucasians and 9320 Asians), we now show that there indeed is a significant difference in prevalence between Caucasians and Asians: 3-fold higher for smell, taste, and “smell and/or taste” impairment in Caucasians (Figure b).…”
Section: Geography Ethnicity and Geneticsmentioning
confidence: 67%
“…The mean or median age of subjects in the 104 studies ranged from 26 to 77 years. Studies reported on subjects from multiple countries (n=5), [15][16][17][18][19] from Australia (n=1), 20 Belgium (n=1), 21 Brazil (n=1), 22 Canada (n=2), 23,24 China (n=7), 2,19,[25][26][27][28][29] France (n=12), 19,[30][31][32][33][34][35][36][37][38][39] Germany (n=10), 19,[40][41][42][43][44][45][46] Greece (n=1), 49 Iceland (n=1), 50 India (n=2) 51,52 Iran (n=3), [53][54][55] Iraq (n=2), 56,57 Israel (n=4), [58][59][60][61] Italy (n=19),…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 34 studies provided information on the severity of COVID-19 disease. Of them, four studies were preprints (Al Harthi et al 2020;Bertlich et al 2020;Papizadeh et al 2020;Patel et al 2020), and 30 articles were published studies (Aggarwal et al 2020;Alasia et al 2021;Alizadehsani et al 2021;Allenbach et al 2020;Amanat et al 2021;Borobia et al 2020;Delorme et al 2021;Elimian et al 2020;Ermis et al 2021;García-Azorín et al 2021;Ghaffari et al 2021;Goyal et al 2021;Izquierdo et al 2020;Kadiane-Oussou et al 2020;Kocayığıt et al 2021;Lechien et al 2021;Liotta et al 2020;Mao et al 2020;McElvaney et al 2020;Muñoz-Rodríguez et al 2021;Printza et al 2021;Romero-Sánchez et al 2020;Salepci et al 2021;Sobhani et al 20212021;Song et al 2021;Studart-Neto et al 2020;Sun et al 2021;Tomlins et al 2020;Vaira et al 2020;Vial et al 2020). The OD were present in 482 severely ill and 2640 non-severely ill patients with COVID-19.…”
Section: Association Between Covid-19 Severity and Losmentioning
confidence: 99%